2015
DOI: 10.1186/1471-2164-16-s10-s1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic species tree estimation in the presence of incomplete lineage sorting and horizontal gene transfer

Abstract: BackgroundSpecies tree estimation is challenged by gene tree heterogeneity resulting from biological processes such as duplication and loss, hybridization, incomplete lineage sorting (ILS), and horizontal gene transfer (HGT). Mathematical theory about reconstructing species trees in the presence of HGT alone or ILS alone suggests that quartet-based species tree methods (known to be statistically consistent under ILS, or under bounded amounts of HGT) might be effective techniques for estimating species trees wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…This coincides with the reason ASTRAL is statistically consistent under the MSC as well as under a model for random HGT [28,8]. Furthermore, previous studies have shown that ASTRAL has good accuracy in simulation studies where both ILS and HGT are present [9]. Hence ASTRAL, which was originally designed for species tree estimation in the presence of ILS, has good accuracy and theoretical guarantees under different sources of gene tree heterogeneity.…”
Section: Discussionsupporting
confidence: 76%
“…This coincides with the reason ASTRAL is statistically consistent under the MSC as well as under a model for random HGT [28,8]. Furthermore, previous studies have shown that ASTRAL has good accuracy in simulation studies where both ILS and HGT are present [9]. Hence ASTRAL, which was originally designed for species tree estimation in the presence of ILS, has good accuracy and theoretical guarantees under different sources of gene tree heterogeneity.…”
Section: Discussionsupporting
confidence: 76%
“…Another direction for future research entails characterizing the conditions under which species tree inference under the MSC is robust to the presence of paralogs in the data.Finally, while we did not discuss or incorporate gene flow in our study, it is possible that all three processes-ILS, GDL, and gene flow-are simultaneously involved in some phylogenomic analyses. Studies of the robustness of MSCbased species tree inference under some models of gene flow exist(Davidson et al, 2015;Roch 2012;SolĂ­s-Lemus et al, 2016;Steel…”
mentioning
confidence: 99%
“…The benefit of such an approach is that it would utilize one of a wide array of species tree inference methods that are both accurate and efficient, thus drastically reducing the space of phylogenetic networks to explore by limiting them to those "based" on inferred trees. Indeed, the question of whether a species tree can be accurately inferred in the presence of reticulation has been partially explored from theoretical [12] as well as empirical [4] angles. An extensive simulation study on small data sets demonstrated the problems with inferring "the" species tree in the presence of high rates of gene flow [13].…”
Section: Introductionmentioning
confidence: 99%
“…One potential approach to tackling the computational requirements of phylogenetic network inference is based on first inferring a "species tree" and then adding a set of reticulation edges to it, in the hope of obtaining the true network. Indeed, as discussed above, the plausibility of this approach has been addressed, albeit in a limited fashion [4,12,6,29,13]. If this approach works in practice, it would tremendously reduce the phylogenetic network space to search and, consequently, scale phylogenetic network inference to much larger data sets.…”
Section: Introductionmentioning
confidence: 99%